Development of E-Module Based on Learning Cycle 6E for the Sub-material of the Distribution of Flora and Fauna in Indonesia and Worldwide for High School Students - Bella, Syintia; Kurnianto, Fahmi Arif; Nurdin, Elan Artono; Astutik, Sri; Apriyanto, Bejo (JPG (Jurnal Pendidikan Geografi), 2024)
This research aims to develop a learning product in the form of an E-Module (Electronic Module) based on the Learning Cycle 6E for the sub-material of the distribution of flora and fauna in Indonesia and worldwide for grade XI high school students with established validity standards. The research method used is Research and Development (R&D) with the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. The analysis stage includes student needs analysis, basic competency analysis, and competency analysis. The design stage involves formulating learning objectives, research and evaluation instruments, and the structure of the E-Module. The development stage includes collecting materials, creating the E-Module, distributing and testing with experts, followed by analysis and revision of the results. The implementation stage involves applying the developed E-Module in a classroom trial with students. The final stage is the evaluation stage, which is conducted to analyze errors during the implementation phase and errors in data collection. This research was conducted at Madrasah Aliyah Negeri 2 Jember with trial subjects being 34 grade XI IPS 4 students. Research instruments used were validation sheets and student response questionnaires. The validation test results of the E-Module by three experts obtained a score of 93.7% for E-Module expert, 98% for content expert, and 100% for learning practitioner, indicating very valid interpretation and suitability for use without revision. The practicality level of the E-Module was determined based on student responses, with a percentage of 92.3% for small group and 93% for large group, categorized as very practical.